(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
An extended inhumation from Baleshare was an adult female with poor dental health and joint disease. At Hornish Point a juvenile had been distributed within four pits. Deliberate disarticulation or butchery was evidenced by cut marks on the fourth and fifth lumbar vertebrae. Animal bone was mainly sheep with cattle, pig, red deer, dog, seal and otter. Many cut marks and burnt bones were identified. A few deposits appear to be deliberate burials of new born animals, of butchery waste and perhaps in one case, of the remains of a funerary feast. A great diversity of fish bones included large shark, gadoids, wrasse, mackerel and several kinds of flatfish. Bird bones included the extinct great auk and crane, along with waterfowl, waders and seabirds.